2009
DOI: 10.1080/18811248.2007.9711552
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of a Single Molten Metal Droplet Penetrating Sodium Pool I Copper Droplet and the Relationship with Copper Jet

Abstract: The progression of hypothetical core disruptive accidents in metallic fuel fast breeder reactors is strongly affected by the fragmentation of molten metallic fuels due to the molten fuel-coolant interaction (FCI). As a basic study of FCI, the present paper focuses on the fragmentation of a single molten copper droplet with mass from 1 to 5 g, which penetrated a sodium pool at instantaneous contact interface temperatures (T i ) from 995 to 1,342 C. Intensive fragmentation of a single molten copper droplet was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Therefore, the fragment size characteristics of molten metal jets can be evaluated reasonably by the fragmentation of the single metal droplet, which has been verified in coppersodium experiments. 5) The present data also link well to the stainless steel data of Armstrong et al 6) despite the mode of streamlets and droplets with large masses from 9.1 to 29.1 g. It is also worth noting that even at T i ¼ 994 C < T tp , one datum of the streamlets and droplets with a D m value of 4.5 mm obtained by Armstrong et al also fairly agrees with the present data. Based on these comparisons, it is suggested that the fragment sizes to be applied for the safety evaluation can be selected without considering the dropping modes and dropping mass of the molten core structural material, provided that the mode of the molten core material and coolant mixing is not significantly different from the presently studied conditions.…”
Section: Size Distributions Of Fragmentssupporting
confidence: 80%
See 4 more Smart Citations
“…Therefore, the fragment size characteristics of molten metal jets can be evaluated reasonably by the fragmentation of the single metal droplet, which has been verified in coppersodium experiments. 5) The present data also link well to the stainless steel data of Armstrong et al 6) despite the mode of streamlets and droplets with large masses from 9.1 to 29.1 g. It is also worth noting that even at T i ¼ 994 C < T tp , one datum of the streamlets and droplets with a D m value of 4.5 mm obtained by Armstrong et al also fairly agrees with the present data. Based on these comparisons, it is suggested that the fragment sizes to be applied for the safety evaluation can be selected without considering the dropping modes and dropping mass of the molten core structural material, provided that the mode of the molten core material and coolant mixing is not significantly different from the presently studied conditions.…”
Section: Size Distributions Of Fragmentssupporting
confidence: 80%
“…5) The relationship between the thermal conditions and the shapes of fragments observed in the present experiment is qualitatively consistent with those observed in the copper-sodium experiments 5) as explained below despite the different thermophysical properties between them.…”
Section: Size Distributions Of Fragmentssupporting
confidence: 79%
See 3 more Smart Citations